Some fishing methods of Mercedes, Camarines Norte. - Neyra, Teodorico A. Jr (College of Fisheries, University of the Philippines, 1953)
In my apprenticeship, I spent most of my time in Mercedes Camarines Norte. The people here having the instinct of skilful fishermen usually used their time in the river either operating a bintol, bubo for catching reef fishes or they joined corporately in a bansigan, an outfit to earn additional or extra income for their livelihood. Fishing has grown to the extent of a major industry in the locality that serves these people to meet their needed prime commodities for other food with what they had realized in fishing. Indeed, the fishing ground is rich in fishes, yet sometimes the operation of a fishing gear is not successful because experience alone cannot meet the modern ways and practices which are applied in commercialized fishing. Nevertheless, methods of fishing in the locality have not been very behind due to the fact that all kinds of modern fishing gear are being utilized for this purpose but the luck of fishing goes with what fishermen know-technical knowhow and practical application of what is thought to be effective along the process of catching these fishes. From fishes, we get nutritional elements and proteins for the bodybuilding. Proper management of our seas which are six times larger than the land surface and with 2,000 species of fishes available or in existence will make the Filipino people healthy, strong and vigorous. Fishes cannot go far from the rice as we Filipinos and will crave for its combination more and more. So conservation must be practiced by all Filipinos so that our national expenses maybe minimized or lessened. Thus, we Filipinos will reduce our import on canned goods from other countries. To prevent the exploitation of our God-given gifts by aliens who are not our fellow nationals we must do something for our own good as a nation. So fisheries in Mercedes and in other places must be cared for and developed properly and efficiently by all owners of fisheries. The fishing industry in Merceeds needs further improvement that would be successful; once and for all time. Thus, when more fishermen will contribute voluntary work for the success and welfare of the fishing industry in Mercedes and elsewhere, we Filipinos will be self-sufficient in fish products and our canned goods imports will be reduce to a minimum. My observations during the period of my six months apprenticeship there are the following gears that existed from the beginnal when methods of fish capture is crude up to the present when The fishermen are feeling general improvement.